Edukasi Pencegahan Penularan Covid-19 Melalui Pembagian Masker Dan Hand Sanitizer Di SDN 2 Padamulya Kabupaten Ciamis - Ayu Rahmawati; Teguh Ikhlas Ramadhan; Ade Rizki Nurmayadi (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Covid-19 is an acute respiratory disease caused by a new type of corona virus. This disease first broke out in Wuhan, China and then spread to almost the entire world and caused a global pandemic. The main symptoms of Covid-19 disease include cough, fever and shortness of breath. The Covid-19 pandemic has brought changes to various aspects of life, one of which is social change. One form of social change that occurred amid the Covid-19 pandemic was the birth of a new normal era. This new lifestyle allows all activities to resume but by implementing strict health protocols. This is the government's effort to keep all activities moving but also continue to try to break the chain of transmission of Covid-19. The purpose of this community service is to improve health status and provide education regarding steps to prevent Covid-19 in the school environment. The method used in this research is descriptive qualitative method. Based on the program, this activity also appealed to all students, teachers and school principals about Clean and Healthy Lifestyles (PHBS) and Hand Washing with Soap (CTPS), using masks and hand sanitizers. To prevent and anticipate the spread of the Covid-19 virus, public awareness is needed to actively implement PHBS and CTPS.